Modeling the human placental barrier to understand Toxoplasma gondii´s vertical transmission - Faral-Tello, Paula; Pagotto, Romina; Bollati-Fogolín, Mariela; Francia, Maria E. (Frontiers in Cellular and Infection Microbiology, 2023)
Toxoplasma gondii is a ubiquitous apicomplexan parasite that can infect virtually any warm-blooded animal. Acquired infection during pregnancy and the placental breach, is at the core of the most devastating consequences of toxoplasmosis. T. gondii can severely impact the pregnancy’s outcome causing miscarriages, stillbirths, premature births, babies with hydrocephalus, microcephaly or intellectual disability, and other later onset neurological, ophthalmological or auditory diseases. To tackle T. gondii’s vertical transmission, it is important to understand the mechanisms underlying host-parasite interactions at the maternal-fetal interface. Nonetheless, the complexity of the human placenta and the ethical concerns associated with its study, have narrowed the modeling of parasite vertical transmission to animal models, encompassing several unavoidable experimental limitations. Some of these difficulties have been overcome by the development of different human cell lines and a variety of primary cultures obtained from human placentas. These cellular models, though extremely valuable, have limited ability to recreate what happens in vivo. During the last decades, the development of new biomaterials and the increase in stem cell knowledge have led to the generation of more physiologically relevant in vitro models. These cell cultures incorporate new dimensions and cellular diversity, emerging as promising tools for unraveling the poorly understood T. gondii´s infection mechanisms during pregnancy. Herein, we review the state of the art of 2D and 3D cultures to approach the biology of T. gondii pertaining to vertical transmission, highlighting the challenges and experimental opportunities of these up-and-coming experimental platforms.